THE TRANSFORMATION OF CULTURAL MEMORY THROUGH THE TRADITIONAL ARCHITECTURE IN MACEDONIA - Namicev, Petar; Namiceva, Ekaterina (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
The transformation of the image of the city or village where human memory is increasingly changing and needs to be adapted to the modern needs and the concept of living. The dynamics of cultural memory in a different context transforms the familiar and beloved buildings in symbols in the context of everyday life. It is necessary to consider the basic elements for the analysis of the transformation of the image of the city and rural areas within the traditional architecture in Macedonia. Through specific examples of the chronology of traditional buildings and historic cores in Macedonia as transformed images of cultural memory, we acknowledge our particular values ​​of the memory image. Thus we find examples where the image of the city is preserved to a greater extent or where the image of the city or rural settlement is completely changed. The guidelines for preserving the optimal level of cultural memory within the traditional architecture are moving towards raising the public awareness, development of cultural policy, modernization of legislation, adapting to urban and spatial planning, development of cultural and rural tourism and inter disciplinary approach for protection of architectural heritage. Keywords: memory, place, tradition, architecture, heritage, building.